Estudio fisiológico de la oxidación del 2-clorofeno por un lodo desnitrificante - Martínez Gutiérrez, Emir (Universidad Autónoma Metropolitana, 2013)
Biological consumption of chlorophenols, compounds generated by various industries such as paper, dyes, pesticides and herbicides, is generally difficult. There are some evidences which indicate that these compounds can be removed from water by methanogenesis or denitrification. In any case, these studies only provide some signs on consumption efficiency, but information about the fate of chlorophenols or the limiting step in the processes is even scarce. The present work provides new experimental evidences which contribute for a better understanding of 2-chlorophenol (2-CP) removal from water. The work consisted of three stages. In all cases denitrifying sludge produced in steady state with no previous exposition to 2-CP was used in batch cultures. At first, it was evaluated the removal of 2-chlorophenol in presence of nitrate, phenol (69 and 92 Cphenol mg/L) or acetate (60 and 108 C-acetate mg/L) as cosubstrate. Specific consumption rate of 2-CP increased in 2.6 and 9 times when phenol or acetate were respectively added, when compared to the control without cosubstrates. Likewise, efficiencies up to 100% were achieved. Denitrifying sludge simultaneously mineralized 2-CP, phenol or acetate whereas nitrate was reduced to N2. In spite of the improvements in 2-CP removal it was not possible to establish if nitrate depletion was linked to the 2- CP removal. In a second stage, it was evaluated in absence of nitrate the effect of different concentrations (77, 127 and 177 mg C/L) of phenol, glucose or acetate on the removal of the 2-chlorophenol (22 mg C/L) under anaerobic conditions. Consumption efficiency of 2-CP increased up to 53.3 %, 97.8% and 98.6% for phenol, glucose and acetate, respectively. Specific consumption rate of 2-CP increased up to 3 and 8.4 times in the assays with glucose and acetate, respectively, as compared to the control without donor electron. The results suggested that electro electron donor type, rather than its concentration determined the 2-CP consumption efficiencies and specific rates values. These effects were not linked to its structural similarity with the 2-CP. On the third stage it was studied the effect of the presence of 2-CP (22 mg C/L) on the denitrifying process, using phenol, acetate o glucose as electron source. In presence of 2-CP, nitrate consumption efficiency (ENO3- ) decrease when glucose or phenol were the electron source, whereas no effect in this parameter was observed with acetate. The nitrate consumption specific rate (qNO3-) decreased in the presence of 2-CP when phenol or glucose were the electron donors whereas the qNO3- increased 1.36 in the assays amended with acetate. Thus, the effect of 2-CP on the denitrifying process was different depending on the electron donor used The results obtained in this work indicated that the cosubstrate had a very important role on the performance for 2-CP mineralization, as the specific oxidation rate of 2-CP was significantly increased. The results showed that the limiting step was the dechlorination and it was verified that phenol is an intermediate of the 2-CP oxidation. Likewise, nitrate was reduced to N2. These evidences might be useful for the biological treatment of wastewaters containing 2-CP.; El consumo biológico de los clorofenoles, compuestos generados por diversas industrias como la del papel, tintes, pesticidas y herbicidas, es generalmente difícil. Existen datos que muestran que por medio de la metanogénesis se pueden eliminar de las aguas residuales. Hay algunos indicios que por medio de la desnitrificación es también posible su eliminación. En cualquier caso, los estudios realizados sólo aportan algunos datos sobre la eficiencia de consumo, pero es poca la información sobre el destino de los clorofenoles y no se cuenta con información suficiente que muestre cuales son los pasos limitantes. En el presente trabajo se aportan nuevas evidencias experimentales que contribuyen a una mejor comprensión de la eliminación del 2-clorofenol (2-CF) en cultivos en lote, utilizando un lodo desnitrificante fisiológicamente estable. El trabajo constó de tres etapas. En la primera se estudió la eliminación del 2-clorofenol (22 mg C/L) en condiciones desnitrificantes iniciales con la presencia de fenol (69 y 92 mg Cfenol/L) o acetato (60 y 108 mg C-acetato/L) como cosustratos. Cuando el fenol fue adicionado, la velocidad específica de consumo del 2-CF se incrementó hasta 2.6 veces con respecto al control sin cosustratos, mientras que con acetato el incremento fue hasta 9 veces con eficiencias hasta de 100%. El lodo desnitifricante mineralizó simultáneamente el 2-CF, fenol o acetato y redujo el nitrato a N2. No obstante, con los resultados obtenidos, no se pudo establecer que el consumo de nitrato estuviera ligado al consumo del 2-CF. En la segunda etapa, se evaluó la eliminación de 2-CF en condiciones anaerobias en ausencia de nitrato y en presencia de diferentes donadores de electrones (fenol, acetato o glucosa) a diferentes concentraciones (77, 127 y 177 mg C/L), para determinar el efecto del tipo y la concentración del donador de electrones sobre el consumo del 2-CF. Los tres donadores de electrones incrementaron la eficiencia de consumo del 2-CF, en comparación con el control sin donador de electrones, con valores de hasta 53.3%, 97,8% y 98.6% en presencia de fenol, glucosa y acetato, respectivamente. Con glucosa y acetato la velocidad de consumo de 2-CF se incrementó, con respecto al control, hasta 3 y 8.4 veces, respectivamente. Los resultados sugirieron que el tipo de donador de electrones, más que su concentración, determinaron los valores de la eficiencia y velocidades específicas y no dependieron de su similitud con el 2-CF. En la tercera etapa se estudió el efecto de la presencia del 2-CF en el proceso desnitrificante, usando fenol, acetato o glucosa como donadores de electrones. En presencia de 2-CF, la eficiencia de consumo de nitrato (ENO3-) disminuyó cuando la glucosa o el fenol fueron la fuente de electrones, mientras que con acetato no se observó un efecto. La velocidad específica de consumo de nitrato (qNO3-) disminuyó en presencia de 2-CF cuando la glucosa o el fenol fueron los donadores de electrones, mientras que la qNO3- se incrementó 1.36 veces en los ensayos con acetato. Así, el efecto del 2-CF sobre el cultivo fue diferente dependiendo del donador de electrones utilizado. Los resultados obtenidos en este trabajo indicaron que el cosustrato tuvo un papel muy importante en la mineralización 2-CF, ya que la velocidad de consumo de 2-CF aumentó significativamente. Los resultados mostraron que el paso limitante fue la descloración y se verificó que el fenol es un intermediario de la oxidación de 2-CF. Estas evidencias pueden ser muy útiles en el tratamiento de aguas residuales que contengan 2- CF.